2019
DOI: 10.1002/aoc.4963
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and chemical characterization of silver nanoparticles from aqueous extract of Falcaria vulgaris leaves and assessment of their cytotoxicity and antioxidant, antibacterial, antifungal and cutaneous wound healing properties

Abstract: Nanotechnology encompasses the understanding of the fundamental physics, biology, chemistry and technology of nanometre‐scale objects. In recent decades, nanotechnology has grown rapidly owing to its widespread application in science and industry. The aim of the work reported was the green synthesis and chemical characterization of silver nanoparticles from aqueous extract of Falcaria vulgaris leaves (AgNPs@Falcaria) and evaluation of their cytotoxicity and antioxidant, antibacterial, antifungal and cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In agreement with the current study, similar studies have shown that phenylhydrazine as an inflammation inducing agent reduces the concentration of anti-inflammatory cytokines and raises the concentration of pro-inflammatory cytokines in serum. [20,28] Both groups of SnNPs and Z. clinopodioides significantly (p ≤ 0.01) improved the levels of pro-inflammatory and anti-inflammatory cytokines to near normal. The best results were observed in SnNPs-treated group.…”
Section: F I G U R Ementioning
confidence: 91%
See 4 more Smart Citations
“…In agreement with the current study, similar studies have shown that phenylhydrazine as an inflammation inducing agent reduces the concentration of anti-inflammatory cytokines and raises the concentration of pro-inflammatory cytokines in serum. [20,28] Both groups of SnNPs and Z. clinopodioides significantly (p ≤ 0.01) improved the levels of pro-inflammatory and anti-inflammatory cytokines to near normal. The best results were observed in SnNPs-treated group.…”
Section: F I G U R Ementioning
confidence: 91%
“…The number of platelets and total WBC also decreased in the phenylhydrazine-treated group. [20,28] SnNPs and Z. clinopodioides ameliorated (p ≤ 0.01) the hematological parameters significantly, so they also significantly (p ≤ 0.01) reduced the number of nRBCs and enhanced the number of total WBC, monocyte, lymphocyte, eosinophil, neutrophil, basophil, RBC, platelet counts and other RBC parameters including Hb,…”
Section: Effect Of Snnps On Hematological and Immunological Parametersmentioning
confidence: 92%
See 3 more Smart Citations